2018
DOI: 10.1016/j.dld.2018.01.132
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of patients with non cirrhotic portal hypertension: Comparison with patients with compensated cirrhosis

Abstract: In the patients with non-cirrhotic PH variceal progression is more rapid and bleeding more frequent than in cirrhotics. Patients with INCPH are particularly prompt to develop PVT. This observational study suggests that the management of patients with non-cirrhotic PH should take into consideration the natural history of portal hypertension in these patients and cannot be simply derived by the observation of cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 28 publications
(27 reference statements)
3
40
1
Order By: Relevance
“…The prevalence of prothrombotic disorders was 35% in our INCPH cohort, which was higher than those reported in previous studies . As shown in the Table S11, the discrepancy was mainly due to the high prevalence of methylene tetrahydrofolate reductase C677T gene mutation in our patients.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The prevalence of prothrombotic disorders was 35% in our INCPH cohort, which was higher than those reported in previous studies . As shown in the Table S11, the discrepancy was mainly due to the high prevalence of methylene tetrahydrofolate reductase C677T gene mutation in our patients.…”
Section: Discussioncontrasting
confidence: 74%
“…Indeed, a recent European multicentre study has shown that TIPSS is an excellent option to treat refractory variceal bleeding in INCPH patients with normal renal function and without severe extrahepatic conditions . However, this recommendation has been challenged by the results of recent studies that the natural history of INCPH, including the variceal progression, development of variceal bleeding, ascites, hepatic encephalopathy and portal vein thrombosis, is not exactly the same as those in cirrhosis . Such differences in natural history may have influence on the TIPSS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients who are first observed for the clinical manifestation of PVT, the possibility that this condition is due to an undiagnosed pre-existing hepatic NCPH is authentic, and it is not usually ruled out by the diagnostic work-up suggested by the current guidelines, which do not routinely include the liver biopsy. (3) In our series, (4) 32% of histologically proven hepatic NCPH developed PVT during the follow-up. The correct diagnosis of PVT secondary to hepatic NCPH may have relevant therapeutic consequences.…”
Section: To the Editormentioning
confidence: 48%
“…Moreover, compression by choledochal or periportal varices of the extrahepatic biliary tree from chronic PVT resulting in portal/biliary cholangiopathy may be associated with increased biliary pressure. (4,5) As pointed out by Gioia et al, patients with PVT have associated subtle histological features, such as phleboclerosis, NRH, sinusoidal dilation, and perisinusoidal or perivenular fibrosis, that could potentially increase the LSM. (6) Although these histological features are less common and may not have much clinical relevance, their effect on LSM is something that needs to be appreciated more in future investigations.…”
Section: Replymentioning
confidence: 99%
“…The BCLC system recommends only transarterial chemoembolization (TACE) and sorafenib for intermediate and advanced HCC, yet several studies have suggested that expanding the selection criteria for hepatectomy can increase overall survival of these patients. Now, an elegant meta-analysis by Hyun and coworkers (4) suggests that, indeed, based on the evidence in 18 high-quality studies, hepatectomy can increase overall survival in patients with intermediate and advanced HCC.…”
Section: Letter To the Editor: Hepatic Resection Compared To Chemoembmentioning
confidence: 99%